Travailler la terre et déconstruire l’hétérosexisme: expérimentations écoféministes - Rimlinger, Constance (Travail, genre et sociétés, 2019)
À partir de l’ethnographie de trois lieux ruraux (deux fermes et un gîte) tenus par des femmes lesbiennes et/ou queer qui s’inscrivent dans une critique écologiste et anticapitaliste de la société tout en questionnant les normes de genre et de sexualité, nous interrogerons la signification de ces choix de vie alternatifs au regard de l’identité des actrices et de la manière dont ils enrichissent la compréhension de la constellation des mouvements écoféministes. Nous observerons qu’avec le déplacement de la ville vers la campagne, et du monde salarié vers l’agriculture de subsistance, elles doivent mettre en place de nouvelles stratégies pour lutter contre l’isolement et s’intégrer localement. Simultanément, ce retour à la terre leur offre de nouvelles possibilités d’émancipation, d’engagement et de soutien aux femmes et aux minorités. Le travail agricole, l’engagement féministe et la politisation du quotidien constituent les différentes facettes d’un même projet : celui de chercher une voie plus juste et plus durable pour notre société.
Keywords: 2000 à aujourd'hui; 2010-2019; agriculture; approches et analyses; care; com5170; cours; discipline; environnement; europe; france; hétérosexisme; premier cycle; périodes historiques; queer; régions géographiques; sciences humaines; sociologie; systèmes d'oppressions; séparatisme lesbien; thématiques; travail; vie rurale; écoféminisme; écologie queer

My butch career: A memoir - Newton, Esther (Duke University Press, 2018)
During her difficult childhood, Esther Newton recalls that she “became an anti-girl, a girl refusenik, caught between genders,” and that her “child body was a strong and capable instrument stuffed into the word ‘girl.’” Later, in early adulthood, as she was on her way to becoming a trailblazing figure in gay and lesbian studies, she “had already chosen higher education over the strongest passion in my life, my love for women, because the two seemed incompatible.” In My Butch Career Newton tells the compelling, disarming, and at times sexy story of her struggle to write, teach, and find love, all while coming to terms with her identity during a particularly intense time of homophobic persecution in the twentieth century. Newton recounts a series of traumas and conflicts, from being molested as a child to her failed attempts to live a “normal,” straight life in high school and college. She discusses being denied tenure at Queens College—despite having written the foundational Mother Camp—and nearly again so at SUNY Purchase. With humor and grace, she describes the influence her father Saul's strong masculinity had on her, her introduction to middle-class gay life, and her love affairs—including one with a well-known abstract painter and another with a French academic she met on a spur-of-the-moment trip to Mexico and with whom she traveled throughout France and Switzerland. By age forty, where Newton's narrative ends, she began to achieve personal and scholarly stability in the company of the first politicized generation of out lesbian and gay scholars with whom she helped create gender and sexuality studies. Affecting and immediate, My Butch Career is a story of a gender outlaw in the making, an invaluable account of a beloved and influential figure in LGBT history, and a powerful reminder of just how recently it has been possible to be an openly queer academic.
Keywords: amériques; approches et analyses; autobiographie; butch; histoire et politique; hétérosexisme; identités LGBTQIA2+; queer; ressource en ligne; régions géographiques; sexualité; systèmes d'oppressions; thématiques; travail; violences; états-unis

Revendiquer la transition de genre comme un travail : ce corps qui n’est pas le mien ? - Hanna, Lou (CONTRETEMPS, 2017)
Chercheuse indépendante en trans et queer studies, militante queer marxiste, dans cet article Lou Hanna tente d’établir un lien entre la transition de genre et le travail. En partant d’une analyse marxiste de l’expropriation de nos corps et de nos vies par le capitalisme néolibéral, il s’agit de tracer une continuité entre performance de genre et travail du genre. Cet article propose ainsi une conception des transidentités en rupture avec un discours hégémonique libéral qui tend à dépolitiser les acquis des luttes issus de l’activisme trans, de plus en plus axé sur une politique des droits au détriment d’une réelle politique révolutionnaire.
Keywords: approches et analyses; cours; discours dominant; europe; fem1300; france; genre; identités LGBTQIA2+; militance; personnes trans*; premier cycle; privilèges; queer; ressource en ligne; régions géographiques; systèmes d'oppressions; thématiques; travail; violences

BLOOD UNDER THE BRIDGE: REFLECTIONS ON “THINKING SEX” - Rubin, Gayle (GLQ: A Journal of Lesbian and Gay Studies, 2011)
This article reflects on the intellectual and political circumstances of the publication of Gayle Rubin's 1984 essay “Thinking Sex: Notes for a Radical Theory of the Politics of Sexuality.” In particular, the article considers the context of the feminist “sex wars” of the late 1970s and early 1980s, offering a detailed account of several of the period's key events, publications, and debates. The article also reflects on the relation between this moment in the history of feminism and the history of GLBT and queer scholarship over the past several decades.
Keywords: 1900-1999; 1960-1969; 1970-1979; LGBTQIA2+; amériques; approches et analyses; cours; discipline; discours dominant; féminisme pro-sexe; histoire et politique; militance; philosophie; premier cycle; périodes historiques; queer; régions géographiques; sciences humaines; sex wars; soc2014; systèmes d'oppressions; thématiques; travail; violences; états-unis; études de genres

Gender & difference in a globalizing world twenty-first century anthropology - Mascia-Lees, Frances E. (Waveland Press, 2010)
"Mascia-Lees'... ability to synthesize ideas rewards readers wih a text that clearly conceptualizes how differences of gender, race, class, and sexuality structure today's complex globalizing world. It exposes the strengths and weaknesses of different theoretical orientations used in anthropology to study gender, difference, power, and inequality including feminist anthropology; black feminist anthropology; lesbian/gay/bisexual/transgendered theory; practice, postcolonial, symbolic, and psychological anthropology; as well as social evolutionism, sociobiology, and evolutionary pscyhology, among others"
Keywords: afro-féminisme; anthropologie; approches et analyses; cours; discipline; féminisme décolonial; histoire et politique; intersectionnalité; premier cycle; queer; sciences humaines; sex1911; sex2283; thématiques; travail

Money, myths, and change: the economic lives of lesbians and gay men - Badgett, Mary Virginia Lee (Worlds of desire, 2001)
How does the standard of living of gay men and lesbians compare with that of heterosexuals? Do homosexuals make financial and family decisions differently? Why are the professional lives of gay men and lesbians dissimilar from those of heterosexuals? Or do they even differ? Have gay people benefited from the recent economic boom? Or have public policies denied them their fair share? Money, Myths, and Change provides new answers to these complex questions. This is the first comprehensive work to explore the economic lives of gays and lesbians in the United States. M. V. Lee Badgett weaves through and debunks common stereotypes about gay privilege, income, and consumer behavior. Studying the ends and means of gay life from an economic perspective, she disproves the assumption that gay men and lesbians are more affluent than heterosexuals, that they inspire discrimination when they come out of the closet, that they consume more conspicuously, that they enjoy a more self-indulgent, even hedonistic lifestyle. Badgett gets to the heart of these misconceptions through an analysis of the crucial issues that affect the livelihood of gay men and lesbians: discrimination in the workplace, denial of health care benefits to domestic partners and children, lack of access to legal institutions such as marriage, the corporate wooing of gay consumer dollars, and the use of gay economic clout to inspire social and political change. Both timely and readable, Money, Myths, and Change stands as a much-needed corrective to the assumptions that inhibit gay economic equality. It is a definitive work that sheds new light on just what it means to be gay or lesbian in the United States.
Keywords: 1900-1999; 1970-1979; 1980-1989; 1990-1999; LGBTQIA2+; amérique du nord; amériques; approches et analyses; capitalisme; cours; discipline; hétéronormativité; hétérosexisme; identités LGBTQIA2+; inégalités; premier cycle; périodes historiques; queer; rapports sociaux de sexe; régions géographiques; shm4000; systèmes d'oppressions; thématiques; travail; états-unis